Settlement of Consumer Disputes According to Law Number 8 of 1999 Reviewed Based on Business Competition Law - Smith, Anita Felicia; Adawiyah, Rodiatun; Ivana, Ivana; Armaini, Agus (IJBLE Scientific Publications Community Inc., 2025)
The Consumer Dispute Settlement Agency (BPSK) holds the authority to resolve consumer disputes through non-litigious means in accordance with Law Number 8 of 1999 concerning Consumer Protection and its implementing regulations. The operational framework of BPSK is explicitly governed by the Minister of Industry and Trade Decree Number 350/MPP/Kep/12/2001. This study aims to analyze the authority and procedures employed by BPSK in resolving consumer disputes, with a particular focus on the BPSK Lubuklinggau City Decision Number: 002/P.Arbitrase/Bpsk-Llg/IV/2021. Employing a normative juridical research approach, this study reviews relevant literature on Consumer Protection Law and Electricity Law. The findings indicate that the authority and resolution process of BPSK require two essential elements: the existence of consumer losses and that such losses arise from the consumption of goods or services provided by business actors. Furthermore, the Lubuklinggau City BPSK Decision Number: 002/P.Arbitrase/Bpsk-Llg/IV/2021 is found to contain formal deficiencies. It is recommended that revisions and harmonization of Law Number 8 of 1999 and other related regulations be undertaken to enhance legal clarity and effectiveness.